Serwis Informacyjny / Biuro Informacyjne MKZ Wrocław . no. 72, 1981 - [ed. Zenon Pałka, Marcjanna Śliwińska, Ksenia Wierzbicka], Biuro Informacyjne NSZZ "Solidarność" Wrocław (BI MKZ, 1981)
Print run: 5000-10000 copies